2013
DOI: 10.1074/jbc.m112.436725
|View full text |Cite
|
Sign up to set email alerts
|

Lytic Activity of the Vibrio cholerae Type VI Secretion Toxin VgrG-3 Is Inhibited by the Antitoxin TsaB

Abstract: Background:The type VI secretion system provides Gram-negative bacteria with a competitive advantage. Results: The V. cholerae T6SS component VgrG-3 has lysozyme-like activity that is inhibited by the product of the downstream gene tsaB. Conclusion: VgrG-3 and TsaB are a toxin-antitoxin complex of the V. cholerae T6SS. Significance: A T6SS effector is characterized along with its cognate antitoxin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
201
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(202 citation statements)
references
References 26 publications
1
201
0
Order By: Relevance
“…In some cases, the same effector can function in bacterial antagonism and also alter cell-signalling pathways in eukaryotic cells (Jiang et al, 2014). Also, 'evolved' VgrGs have been described that contain various C-terminal extensions leading, for instance, to actin cross-linking or actin-ADP ribosylation in eukaryotic cells (Brooks et al, 2013;Pukatzki et al, 2007;Suarez et al, 2010), and host cell fusion presumably to facilitate intercellular bacterial spreading (Schwarz et al, 2014;Toesca et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, the same effector can function in bacterial antagonism and also alter cell-signalling pathways in eukaryotic cells (Jiang et al, 2014). Also, 'evolved' VgrGs have been described that contain various C-terminal extensions leading, for instance, to actin cross-linking or actin-ADP ribosylation in eukaryotic cells (Brooks et al, 2013;Pukatzki et al, 2007;Suarez et al, 2010), and host cell fusion presumably to facilitate intercellular bacterial spreading (Schwarz et al, 2014;Toesca et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It may feature the effector function at the C-terminal domain. Such "evolved VgrGs" include Vibrio cholerae VgrG-1, with an actin cross-linking domain; Aeromonas hydrophila VgrG1, with an actin-ADP ribosylating VIP-2 domain; and V. cholerae VgrG-3, with glycoside hydrolase activity to target peptidoglycan (9,(25)(26)(27). Furthermore, VgrG may function as a carrier for effector delivery by binding directly with specific effectors carrying the proline-alanine-alanine-arginine (PAAR) domain (28,29).…”
mentioning
confidence: 99%
“…The product was cloned between the NcoI and XhoI restriction sites of the expression vector pET-28a (Novagen) with a hexahistidine tag at the C-terminus as described previously (Brooks et al, 2013). After sequencing, the plasmid was transformed into Escherichia coli BL21 (DE3) competent cells (Novagen, USA).…”
Section: Cloning and Expressionmentioning
confidence: 99%
“…Subsequently, it was reported that TsiV3 (TsaB) directly binds to and inhibits effector protein VgrG-3 in a type II toxin-antitoxin (TA) manner and thus presents immunity to the toxic activity of VgrG-3 (Brooks et al, 2013). As a novel T6SS immunity protein, TsiV3 does not share high sequence identity with other immunity proteins of known structure (Q9I2Q0, C6BHF3, Q8ZRL5, Q9HYC4, Q4KC91 and Q9I0D9; Shang et al, 2012;Dong, Zhang et al, 2013;Zhang et al, 2013;Wang et al, 2013;Whitney et al, 2013;Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation